Some Techniques to Compute Multiplicative Inverses for Advanced Encryption Standard - Ahmed, Waleed Eltayeb (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
This paper gives some techniques to compute the set of multiplicative inverses, which uses in the Advanced Encryption Standard (AES).